(3GdfXGe GdbGfhfi deHOC EbdjejI bhGYO h CMcGe GdEadGS (B: s (3OQGSI ebGQfI habG ddbGfhf GdeUQi h GdLghO GdOhdjI (B/ s - (3CMeO HZOGOi QTOi CMeOs; (3SejMI eUWai GdbdjhHi s; (3gGfi UdGM SQi GdOjf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3JfGhd gPG GdHMK OQGSI JfXje bhGYO h CMcGe GdGadGS GdYGHQ ddMOhO GdJi JHfi GdeTQY GdeUQi HUOOgG eHOC GbdjejI GdGadGS habG ddeGOI (B559/ 2 (3ef bGfhf GdJLGQI Qbe (B17(3dSfI (B1999(3h GdJi fbdJ HPGJgG Gdi fU GdeGOI GdKGfjI ef bGfhf GdEadGS GdLOjO GdbGfhf Qbe (B11(3dSfI (B2018 (3HGUOGQ bGfhf GYGOI GdgjcdI h GdUdM GdhGbi h GdGadGS(B. (3h bO JYQV GdHMK deaghe eHOC GdGbdjejI HUaI YGeI ai JWHjb GdbhGfjf(B: (3Ke GdfXQjJGf GdMGceJGf ddGadGS YHQ GdMOhO h geG fXQjI GbdjejI GdGadGS h fXQjI YGdejI GdGadGS(B: (3h ehba GdbGfhf h GdbVGA GdeUQi h GdebGQf efgeG(B: (3h YQV dGge GdGTcGdjGJ GdfGLeI Yf JWHjb eHOC GdGbdjeI GdeJYdbI HJMOjO GdeMceI GdeNJUI HETgGQ GdEadGS(B: (3h BKGQ GdMce GdUGOQ ai EMOi GdOhd(B: (3h ETcGdjGJ JJYdb HGJLGg eYXe GdTQcGJ eJYOOI GdLfSjGJ Edi GdGJaGb Ydi GdJMcje chSjdI dMd GdfRGYGJ GdfGTFI Yf eeGQSI fTGWgG ai GdHdO GdeVja(B: (3h CKQ UOhQ Mce HGdEadGS Ydi OYGhi GdJMcje GdbGFeI CeGe gjFGJ GdJMcje(B. (3ceG JfGhd GdHMK GdGJLGg GdMOjK ai GdJTQjYGJ GdebGQfI (B- (3cGdbGfhfjf GdGeQjci h GdHdLjci (B- (3GdJi JHfJ fXQjI YGdejI GdGadGS h GdGYJQGa HGMcGe GdGadGS GdGLfHjI JaGOjG ddGTcGdjGJ GdJi fLeJ Yf JWHjb eHOC GdGbdjejIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2018(3, bSe GdbGfhf GdJLGQjs
(3HHdjhLQGajG(B: (3UaMGJ (B360-373s
Keywords: (3GdbGfhf GdfehPLjs; (3GdEadGSs; (3GdJadjSIs; (3GdGhfSjJQGds; (3dGFMI GdeLdS GdGhQhHj dELQGAGJ GdGadGSs; (3fXQjI hMOI GdGadGSs; (3fXQjI JYOO GdGadGSs; (3TgQ GdGYSGQs; (3GdGSJKeGQ GdGLfHjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs